Optimalisasi Pajak Daerah sebagai Instrumen Hukum dalam Penguatan Kemandirian Fiskal Pemerintah Daerah - Nita Cicilia Ganap; Shintia AlverniaG. Gijoh; Kristiane Aprilia Paendong; Joice Jane Umboh; Cindy Mariam M. Rantung (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
This study aims to analyze the optimization of local taxes as a legal instrument in realizing the fiscal independence of local governments and to examine the juridical factors that hinder their implementation in regional governance. This research employs a normative legal method using statutory, conceptual, and analytical approaches. The legal materials consist of primary, secondary, and tertiary legal sources analyzed qualitatively through descriptive-analytical and prescriptive methods. The results show that local taxes hold a strategic role in strengthening regional fiscal capacity, supporting the effectiveness of regional autonomy, and enhancing regional development based on fiscal decentralization. The optimization of local taxes can be achieved through strengthening local tax regulations, digitalizing tax administration systems, improving law enforcement quality, and developing public tax awareness. However, the implementation of local taxes still faces several juridical obstacles, including regulatory disharmony, weak law enforcement, low quality of local regulations, limited capacity of local government officials, and low public trust in local tax management. Therefore, legal reform of local taxation based on transparency, accountability, and good local governance is essential to support the fiscal independence of local governments and sustainable national development..